2020
DOI: 10.3389/fcell.2020.588544
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin-4 Promotes the Progression of Prostate Cancer Through the Akt/GSK-3β/β-Catenin Signaling Pathway

Abstract: The first-line treatment for prostate cancer (PCa) is androgen ablation therapy. However, prostate tumors generally recur and progress to androgen-independent PCa (AIPC) within 2–3 years. α-Actinin-4 (ACTN4) is an actin-binding protein that belongs to the spectrin gene superfamily and acts as an oncogene in various cancer types. Although ACTN4 is involved in tumorigenesis and the epithelial–mesenchymal transition of cervical cancer, the role of ACTN4 in PCa remains unknown. We found that the ACTN4 expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Recent studies have also correlated ACTN4 with some additional, somehow unexpected pleiotropic signaling roles. Epigenetically, ACTN4 has been found to act as a transcriptional co‐activator of the Akt/GSK‐3β/β‐catenin pathway (S. Park et al, 2020) and the p65 subunit of NF‐κΒ (Aksenova et al, 2013). Moreover, it also acts as a regulator of nuclear mRNA metabolism (Khotin et al, 2010) through the binding to the promoter of the cytochrome c gene upon muscle differentiation (Goffart et al, 2006), and the regulation of CYP1A1 gene expression (Poch et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also correlated ACTN4 with some additional, somehow unexpected pleiotropic signaling roles. Epigenetically, ACTN4 has been found to act as a transcriptional co‐activator of the Akt/GSK‐3β/β‐catenin pathway (S. Park et al, 2020) and the p65 subunit of NF‐κΒ (Aksenova et al, 2013). Moreover, it also acts as a regulator of nuclear mRNA metabolism (Khotin et al, 2010) through the binding to the promoter of the cytochrome c gene upon muscle differentiation (Goffart et al, 2006), and the regulation of CYP1A1 gene expression (Poch et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, both LIMK 1 and LIMK 2 are found in the nucleus. As in cytoplasmic signaling, Rho GTPases also function in nuclear signaling, especially in DNA damage/repair, a process in which cofilin has also been implicated [250], so a pathway for LIMK phospho-activation via a Rho GTPase effector such as ROCK/PAK likely mediates the aspects of this process [251] (Figure 8). Surprisingly, evidence suggests LIMK1 and LIMK2 affect nuclear function but in opposite directions, with an imbalance proposed to affect cell proliferation and metastasis in some cancers [252,253].…”
Section: Cofilin Organelle Localization and Functional Consequences 71 Nucleusmentioning
confidence: 99%
“…It was shown that ACTN4 expression level was higher in DU145 cells and PC-3 cells than in LNCaP cells (8). Sungyeon Park et al also verified that the protein level of ACTN4 was increased in LNCaP-AI cells compared with LNCaP cells (23). A previous study reported that ACTN4 interacts with glucocorticoid receptor and plays a role in glucocorticoid receptor activation (51).…”
Section: The Expression Pattern Of Emerging Proteins In Cell Linesmentioning
confidence: 92%
“…Some proteins have been found expressed differently between CSPC and CRPC by traditional techniques such as WB. ACTN4, a member of the spectrin gene superfamily, always acts as an oncogene in various cancer types (23). To identify novel therapeutic targets for CRPC, Yu Ishizuya et al applied WB to examine the expression of ACTN4 in four prostate cancer cell lines (8).…”
Section: The Expression Pattern Of Emerging Proteins In Cell Linesmentioning
confidence: 99%